Stability of masking materials for pattern transfer of lithographic masks into fused silica by atmospheric pressure plasma jet etching - Robert Heinke; Lukáš Šilhan; Martin Ehrhardt; Pierre Lorenz; Joachim Zajadacz; Jens Bauer; Thomas Arnold; Mojmír Šerý; Klaus Zimmer (Micro and Nano Engineering, 2025)
Masking of thin films and bulk materials is traditionally applied for the transfer of micron patterns into the functional material according to the requirements of the application. For optical purposes, lithographically produced micron patterns are transferred by plasma/ion etching, which is a traditional technology in microelectronics and other micron technologies. However, pattern transfer by atmospheric pressure plasma etching can help to save time and cost for a future sustainable production. Therefore, the pattern transfer of lithographic resist masks into fused silica using atmospheric pressure reactive plasma jets (APPJ) was studied as a new approach of micropatterning. First the etch rates of the potential masking materials, e.g. photoresists, as well as of fused silica as substrate are studied in dependence on the APPJ etching parameters, in particular on the gas composition (O2/CF4) and the dwell time of the APPJ tool's footprint. Typical etch rates of the masking materials are in the range of 140 to 370 nm·s−1 whereas the fused silica has a rate of 25 to 80 nm·s−1. The surface morphology of masking materials changes during etching and features additional nanoscale roughness and waviness. The surface roughness of the etched masking materials and the fused silica are 2 to 5 nm rms and 1.5 nm rms for etch depths of ∼3000 nm and ∼ 600 nm, respectively. Finally, the pattern transfer by APPJ of a diffraction grating with a period of 15 μm, depth of 230 nm and a roughness below 2 nm rms into fused silica was demonstrated.
Keywords: AIF; MF

Simulation of optomechanical interaction of levitated nanoparticle with photonic crystal micro cavity - Tadeáš Maňka; Martin Šiler; Vojtěch Liška; Pavel Zemánek; Mojmír Šerý; Oto Brzobohatý (Opt. Express, 2024)
We propose and analyze theoretically a promising design of an optical trap for vacuum levitation of nanoparticles based on a one-dimensional (1D) silicon photonic crystal cavity (PhC). The considered cavity has a quadratically modulated width of the silicon wave guiding structure, leading to a calculated cavity quality factor of 8 × 105. An effective mode volume of approximately 0.16 μm3 having the optical field strongly confined outside the silicon structure enables optical confinement on nanoparticle in all three dimensions. The optical forces and particle-cavity optomechanical coupling are comprehensively analyzed for two sizes of silica nanoparticles (100 nm and 150 nm in diameter) and various mode detunings. The value of trapping stiffnesses in the microcavity is predicted to be 5 order of magnitudes higher than that reached for optimized optical tweezers, moreover the linear single photon coupling rate can reach MHz level which is 6 order magnitude larger than previously reported values for common bulk cavities. The theoretical results support optimistic prospects towards a compact chip for optical levitation in vacuum and cooling of translational mechanical degrees of motion for the silica nanoparticle of a diameter of 100 nm.
Keywords: LF; MF

Rapid identification of pathogens in blood serum via Raman tweezers in combination with advanced processing methods - Ondřej Vaculík; Silvie Bernatová; Katarína Rebrošová; Ota Samek; Lukáš Šilhan; Filip Rů žička; Mojmír Šerý; Martin Šiler; Jan Jež ek; Pavel Zemánek (Biomed. Opt. Express, 2023)
Keywords: AIF; BF; LF; MF

Label-free CARS microscopy through a multimode fiber endoscope - Johanna Trägårdh; Tomáš Pikálek; Mojmír Šerý; Tobias Meyer; Jürgen Popp; Tomáš Čižmár (Opt. Express, 2019)
Multimode fibres have recently been employed as high-resolution ultra-thin endoscopes, capable of imaging biological structures deep inside tissue in vivo. Here, we extend this technique to label-free non-linear microscopy with chemical contrast using coherent anti-Stokes Raman scattering (CARS) through a multimode fibre endoscope, which opens up new avenues for instant and in-situ diagnosis of potentially malignant tissue. We use a commercial 125 µm diameter, 0.29 NA GRIN fibre, and wavefront shaping on an SLM is used to create foci that are scanned behind the fibre facet across the sample. The chemical selectivity is demonstrated by imaging 2 µm polystyrene and 2.5 µm PMMA beads with per pixel integration time as low as 1 ms for epi-detection.
Keywords: KF; MF